Calcule o produto :
(x²-2).(3x³-x+1)
me ajudemm ❤
Soluções para a tarefa
Respondido por
10
veja...
(x²-2)(3x³-x+1)=
x²(3x³-x+1)-2(3x³-x+1)
3x⁵-x³+x²-6x³+2x-2=
3x⁵-x³-6x³+x²+2x-2=
3x⁵-7x³+x²+2x-2
(x²-2)(3x³-x+1)=
x²(3x³-x+1)-2(3x³-x+1)
3x⁵-x³+x²-6x³+2x-2=
3x⁵-x³-6x³+x²+2x-2=
3x⁵-7x³+x²+2x-2
FláviaFernandes7899:
Mt obrigadoo ❤
Perguntas interessantes
Geografia,
11 meses atrás
História,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás